ANALISIS PERLINDUNGAN HUKUM TERHADAP DEBITUR DENGAN ITIKAD BAIK DALAM PENARIKAN PAKSA OLEH (PIHAK KE III) DALAM PERIKATAN FIDUSIA (STUDI PUTUSAN NOMOR 63.Pdt.G.S/2025/PN Serang) - Suhartoyo; Iron Fajrul Aslami; Safiulloh (Ajudikasi: Jurnal Ilmu Hukum, 2026)
This research is motivated by the widespread practice of third parties (debt collectors) forcibly withdrawing fiduciary collateral objects without complying with legal procedures, thereby potentially harming debtors with good intentions and creating legal uncertainty. This study aims to analyze the validity of the execution of fiduciary collateral without a summons or court order, as well as the form of legal protection for debtors under Decision Number 63/Pdt.G.S/2025/PN Serang. The research uses a normative legal method with a statutory, conceptual, and case approach. Primary, secondary, and tertiary legal materials are analyzed qualitatively using a descriptive-analytical method. The results of the study indicate that the execution of fiduciary collateral without a summons, without a default agreement, without voluntary surrender of collateral objects by the debtor, and without a court mechanism is contrary to Law Number 42 of 1999 concerning Fiduciary Guarantees and Constitutional Court Decision Number 18/PUU-XVII/2019 in conjunction with Constitutional Court Decision Number 2/PUU-XIX/2021. Forced withdrawal by a third party under these circumstances constitutes an unlawful act because it violates the debtor's rights and the principle of due process of law. Legal protection is provided through preventive mechanisms, including the regulation of legitimate execution procedures, and through repressive measures, including lawsuits to obtain rights restoration and compensation. Therefore, the enforcement of fiduciary guarantees must be carried out in accordance with the law to ensure legal certainty, justice, and protection for debtors acting in good faith